2022
DOI: 10.1002/da.23260
|View full text |Cite
|
Sign up to set email alerts
|

Association of disease course and brain structural alterations in major depressive disorder

Abstract: Introduction The investigation of disease course‐associated brain structural alterations in Major Depressive Disorder (MDD) have resulted in heterogeneous findings, possibly due to low reliability of single clinical variables used for defining disease course. The present study employed a principal component analysis (PCA) on multiple clinical variables to investigate effects of cumulative lifetime illness burden on brain structure in a large and heterogeneous sample of MDD patients. Methods Gray matter volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
2
7
1
Order By: Relevance
“…Notably, only a small sample of 27 FED patients and 17 HC was investigated. The results of this study stand in contrast to former literature reporting GMV alterations in FED patients compared with HC [21][22][23][24], and GMV changes associated with disease progression [8][9][10][11][12][13][14][15][16].…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, only a small sample of 27 FED patients and 17 HC was investigated. The results of this study stand in contrast to former literature reporting GMV alterations in FED patients compared with HC [21][22][23][24], and GMV changes associated with disease progression [8][9][10][11][12][13][14][15][16].…”
Section: Introductioncontrasting
confidence: 99%
“…While cross-sectional research in MDD repeatedly showed that decreased gray matter volumes (GMV) and (sub-)cortical thickness are associated with more severe lifetime disease trajectories [6][7][8][9][10], the direct interplay between neural changes and recurrence remains unclear. Previous longitudinal studies reported morphometric changes [11], for example, in the dorsolateral prefrontal cortex (DLPFC), insula, hippocampus, and anterior cingulate cortex, showing greater GMV decline in dependence of more detrimental disease courses [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We leveraged a relatively large LLD sample (n = 426) with SASP protein measurements. Following previous studies demonstrating the utility of integrating various variables [32][33][34] , we used factor analyses to group clinical variables. We then tested our hypothesis that the resulting clinical factors would be associated with the SASP index.…”
Section: Articlementioning
confidence: 99%
“…associating neuroimaging markers with long-term disease trajectories. [8,[56][57][58] Likewise, investigating symptoms rather than syndromes has been promoted lately, with network theory of psychopathology providing one conceptual framework possibly able to model symptom dynamics independent of psychiatric category. [59] Indeed, our results regarding correlations of misclassification frequency provide support for associations between symptom severity and neurobiological markers, suggesting that patients with higher levels of current symptoms, lower global functioning and more unfavourable disease courses in the past are easier to detect and correctly classify.…”
Section: Discussionmentioning
confidence: 99%